Complementary Molecular Data for Two Species from Herbarium Bogoriense: Sphaerobolus stellatus and Trichaleurina javanica - Meta Yuliana; Indra Maulana; Sari Mulya; Laifa Fusvita; Rudy Hermawan (Jurnal Biologi Universitas Andalas, 2024)
A micro-mushroom namely Sphaerobolus stellatus (BO 24422) and macro-mushroom namely Trichaleurina javanica (BO 24420) were found in Landscape Arboretum of IPB University. The latest identification used morphological characteristic and molecular study of Large Subunit DNA marker respectively. According to their identification, the database of fungal identification is commonly from Internal Transcribed Spacer (ITS) marker for molecular study. But both specimens, S. stellatus BO 24422 and T. javanica BO 24420, have not the ITS sequences yet. This research aim to study the molecular data of two specimens using ITS sequences. The method of this research used the molecular identification using internal transcribed spacer (ITS) primer: ITS 4 as a forward and ITS 5 as a reverse. Two phylogenetic trees were generated by Randomized Axelarated Maximum Likelihood (RAxML) Black box. Bootstrap (BS) values ≥ 90% were displayed on the phylogenetic treebranches. The result showed that the bootstrap value for S. stellatus BO 24422  showed the good value as 96% classified as S. stellatus. Then, T. javanica BO 24420  had a better BS value with 93% classified as T. javanica. The ITS is a general marker and very useful for molecular identification.